(untitled) (Jurnal Teknologi (Sciences & Engineering), 2012)
Surface discharge is a common electrical discharge that normally occurs on outdoor insulators under wet and contaminated conditions. The dry–band discharge exists because of the leakage current that flows on the insulator surface. Measuring the surface leakage current can identify the performance of insulating materials as well as the characteristics of discharges. A computer–based on–line monitoring of surface leakage current is found to be more practical due to the long period of time taken in conducting the laboratory test. This paper describes the design and development of a leakage current monitoring system associated with surface tracking and erosion resistance test set–up of IEC 587. The LabVIEW software package is used to develop a measurement program for recording and analysing leakage current signals. Experimental works have shown the capability of the developed system in detecting the performance of insulating materials as well as identifying the characteristics of the surface discharges. Besides the on–line monitoring function, a data storage feature is also added to the system to allow for further analysis. Key words: surface discharge; leakage current; signal analysis; virtual instrument program